2023
DOI: 10.1182/bloodadvances.2022009253
|View full text |Cite
|
Sign up to set email alerts
|

T-cell replete cord transplants give superior outcomes in high-risk and relapsed/refractory pediatric myeloid malignancy

Abstract: Stem cell transplant (SCT) outcomes in high-risk (HR) and relapsed/refractory (R/R) paediatric acute myeloid leukaemia (AML) and myelodysplastic syndrome (MDS) have been poor historically. Cord blood allows T-cell replete transplant (TRCB), enabling enhanced graft-versus-leukaemia. We collected data from 367 consecutive patients undergoing TRCB (112 patients) or other cell source (255 patients) SCT for paediatric AML/MDS in the UK and Ireland between January 2014 and December 2021. Data was collected about pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…In this issue of Blood Advances , through a multicenter analysis of 367 pediatric patients, Horgan et al have reported that T-replete umbilical cord stem cell (TRCB) transplants against myeloid disease provide superior disease-free survival and event-free survival (EFS) compared with that provided by all other donor sources, including matched unrelated donor, matched sibling donor, mismatched unrelated donor, haploidentical, and T-depleted cord. 1 Similar to other reports, in young and adult patients from single institutions, the power of cord-derived T cells during transplantation appeared greatest in those children with measurable residual disease (MRD) before transplant. 2 Horgan et al found similar EFS and overall survival in patients from all groups who had no MRD before transplant, including those who received transplants using other alternative donor sources, including haploidentical grafts.…”
supporting
confidence: 80%
“…In this issue of Blood Advances , through a multicenter analysis of 367 pediatric patients, Horgan et al have reported that T-replete umbilical cord stem cell (TRCB) transplants against myeloid disease provide superior disease-free survival and event-free survival (EFS) compared with that provided by all other donor sources, including matched unrelated donor, matched sibling donor, mismatched unrelated donor, haploidentical, and T-depleted cord. 1 Similar to other reports, in young and adult patients from single institutions, the power of cord-derived T cells during transplantation appeared greatest in those children with measurable residual disease (MRD) before transplant. 2 Horgan et al found similar EFS and overall survival in patients from all groups who had no MRD before transplant, including those who received transplants using other alternative donor sources, including haploidentical grafts.…”
supporting
confidence: 80%
“…We have previously reported that relapse risk is reduced following CBT for myeloid malignancy 4 . It remains, however, the commonest cause of treatment failure.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported that relapse risk is reduced following CBT for myeloid malignancy. 4 It remains, however, the commonest cause of treatment failure. We have previously serendipitously noted and reported T-cell expansion in patients receiving granulocytes during CBT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations